2020
DOI: 10.3389/fnhum.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Eye-to-Eye Contact Is Associated With Cross-Brain Neural Coupling in Angular Gyrus

Abstract: Direct eye contact between two individuals is a salient social behavior known to initiate and promote interpersonal interaction. However, the neural processes that underlie these live interactive behaviors and eye-to-eye contact are not well understood. The Dynamic Neural Coupling Hypothesis presents a general theoretical framework proposing that shared interactive behaviors are represented by cross-brain signal coherence. Using functional near-infrared spectroscopy (fNIRS) adapted for hyper scanning, we teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 69 publications
(102 reference statements)
4
94
0
Order By: Relevance
“…The experimental paradigm was similar to previously reported two-person interaction paradigms ( Hirsch et al , 2017 , 2018 ; Piva et al , 2017 ; Noah et al , 2020 ). Participants were positioned approximately 140 cm across a table from each other with a full view of their partner’s face.…”
Section: Methodsmentioning
confidence: 93%
“…The experimental paradigm was similar to previously reported two-person interaction paradigms ( Hirsch et al , 2017 , 2018 ; Piva et al , 2017 ; Noah et al , 2020 ). Participants were positioned approximately 140 cm across a table from each other with a full view of their partner’s face.…”
Section: Methodsmentioning
confidence: 93%
“…Here, we examine the role of social eye-to-eye contact behavior as a modulator of joint attention mechanisms to test the hypothesis that the two mechanisms are synergistic. Based on prior studies of eye contact, we have previously shown that direct, mutual eye contact engages the visual and social systems during social interaction (Hirsch et al, 2017;Noah et al, 2020). This predicts increased social exchange between participants who engage in increased eye contact, and these participants may recruit these areas more than in less social participants who make fewer eye contacts during a social joint attention task.…”
Section: Introductionmentioning
confidence: 94%
“…Analysis methods for fNIRS data were similar to those previously reported and are explained in detail elsewhere (Dravida et al, 2017;Hirsch et al, 2017Hirsch et al, , 2018Noah et al, 2017Noah et al, , 2020. The signal used for the analysis was the combined hemoglobin signal, the sum of the oxyhemoglobin and the inverted deoxyhemoglobin signals.…”
Section: Functional Near-infrared Spectroscopy Analysismentioning
confidence: 99%
“…As shown in Figure 1 , the distribution of hyperscan conditions dedicated to each of the nine categories defined by our framework is highly unequal. Over half of all reported hyperscan conditions (57.8%, N = 87) were conducted when the interacting dyad were in the same room without any means of digital interaction (i.e., Analog ToI) (Funane et al, 2011 ; Holper et al, 2012 , 2013 ; Jiang et al, 2012 , 2015 ; Osaka et al, 2014 , 2015 ; Duan et al, 2015 ; Liu N et al, 2016 ; Nozawa et al, 2016 , 2019 ; Hirsch et al, 2017 , 2018 ; Ikeda et al, 2017 ; Zhang et al, 2017a , b ; Zhao et al, 2017 ; Dai et al, 2018a , b ; Fishburn et al, 2018 ; Pan et al, 2018 , 2020a ; Xue et al, 2018 ; Zhang Y et al, 2018 ; Lu et al, 2019 , 2020 ; Mayseless et al, 2019 ; Niu et al, 2019 ; Vanzella et al, 2019 ; Noah et al, 2020 ), while (42.4%, N = 64) included some element of technology (e.g., playing a computer game) while participants were in the same room (Cui et al, 2012 ; Dommer et al, 2012 ; Duan et al, 2013 ; Cheng et al, 2015 , 2019 ; Liu T et al, 2015 , 2016 , 2017 ; Baker et al, 2016 ; Tang et al, 2016 ; Balconi and Vanutelli, 2017a , b ; Hu et al, 2017 ; Pan et al, 2017 , 2020b ; Piva et al, 2017 ; Takeuchi et al, 2017 ; Fishburn et al, 2018 ; Zhang M et al, 2018 ; Zheng et al, 2018 , 2020 ; Balconi et al, 2019 ; Liu et al, 2019 ; Nozawa et al, 2019 ; Sarinasadat et al, 2019a …”
Section: Deriving An Fnirs Hyperscanning Frameworkmentioning
confidence: 99%
“…However, the classification of the comparisons reported were limited to Analog vs. Mixed and Inter-ToI comparisons. The studies comprised comparisons between Mixed ToI/Joint goal-driven ToC and Mixed ToI/Mixed ToC ( N = 5) (Cui et al, 2012 ; Cheng et al, 2015 ; Liu T et al, 2015 , 2016 , 2017 ), Analog ToI/Mixed ToC and Analog ToI/Joint goal-driven ToC ( N = 7) (Jiang et al, 2012 ; Holper et al, 2013 ; Osaka et al, 2014 , 2015 ; Hirsch et al, 2018 ; Niu et al, 2019 ; Vanzella et al, 2019 ), Analog ToI/Joint open-ended ToC and Analog ToI/Joint goal-driven ToC ( N = 3) (Liu N et al, 2016 ; Ikeda et al, 2017 ; Zhang Y et al, 2018 ), and Analog ToI/Mixed ToC and Mixed ToI/Joint goal-driven ToC ( N = 2) (Nozawa et al, 2019 ; Noah et al, 2020 ). Two studies included three cross-condition comparisons, including comparisons between Analog ToI/Mixed ToC, Analog ToI/Joint goal-driven ToC, and Mixed ToI/Joint open-ended ToC ( N = 1) (Fishburn et al, 2018 ), as well as between Analog ToI/Joint goal-driven ToC, Analog ToI/Joint open-ended ToC, and Mixed ToI/Joint goal-driven ToC ( N = 1) (Yang et al, 2020 ).…”
Section: Deriving An Fnirs Hyperscanning Frameworkmentioning
confidence: 99%